IMPLEMENTASI PERATURAN DAERAH KOTA BANDAR LAMPUNG NOMOR 01 TAHUN 2011 TENTANG PAJAK DAERAH (Studi Pada Kecamatan Tanjung Karang Pusat) - Agus Iskandar (KEADILAN PROGRESIF, 2019)
Tax is a levy from the public to the state (government) based on laws that areenforceable and payable by those who are obliged to pay it with no immediate performance(counter performance / remuneration), the results of which are used to finance stateexpenditure in government administration and development. The problem in this research ishow the implementation of the Bandar Lampung City Regional Regulation Number 01 of2011 concerning Regional Taxes. The method used by the normative juridical approach andanalysis is done qualitatively. The results showed that the enactment of Regional RegulationNumber 01 of 2011 in managing regional own-source revenue with the aim of increasingregional income, and the results of the acquisition of land and building tax for TanjungKarang Pusat Sub-district had not been maximized from the target set due to obstaclesencountered by collectors in tax collection owed to taxpayers because taxpayers object to theLand and Building Tax that is set